THE EFFECT OF WORK DISCIPLINE AND INTERPERSONAL COMMUNICATION OF EMPLOYEE PERFORMANCE PT. NOK INDONESIA PRODUKSI 2 - Tri Wahju Wirjawan; Preatmi Nurastuti (SEAN Institute, 2022)
Success is not a company that is determined from the results that have been determined by the company. Company goals can be seen from the results according to the specified target or not. Interpersonal communication. Good work discipline, good company performance improvement also increases. Interpersonal communication that is well established, will facilitate performance because of the positive feedback from all employees. The purpose of this study is to study work discipline and interpersonal communication on employee performance. The research data were collected using the method of observation and questionnaire distributed to 60 respondents who were submitted to the employees of PT. NOK Indonesia. Before conducting research, an instrument test is first performed to determine the level of validity and reliability. Then the data is announced normality so that it can be known whether the data is normally distributed. After that, a multiple regression test, a t test, and an F test and a coefficient of determination. Based on the results of the regression test on work discipline participation and interpersonal communication on employee performance by 44%. The rest, employee performance, is by other variables not supported in this study.